2022
DOI: 10.3390/curroncol29100589
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Mediterranean Diet and Nutritional Status in Women with Breast Cancer: What Is Their Impact on Disease Progression and Recurrence-Free Patients’ Survival?

Abstract: Introduction: Nutritional status impacts the survival of patients with cancer. There are few studies that investigate the role of nutritional status on breast cancer survival in women with breast cancer, and even fewer regarding the impact of adhering to the Mediterranean diet (MD). The present study aims to assess the nutritional status, MD adherence, physical activity levels and health-related quality of life (HRQOL) in women diagnosed with breast cancer and evaluate these parameters regarding recurrence-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Although, it should be noted that there were some improvements over time in the control group as well, with respect to avoiding added sugars and reducing GL, suggesting that the educational materials alone may have also had some beneficial effects on dietary habits. The value of diet in survivorship is highlighted by data suggesting improvement in overall survival among breast cancer survivors who adhere to healthy dietary habits ( 67 ). Unfortunately, the majority of breast cancer survivors fail to adhere to ACS dietary recommendations ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, it should be noted that there were some improvements over time in the control group as well, with respect to avoiding added sugars and reducing GL, suggesting that the educational materials alone may have also had some beneficial effects on dietary habits. The value of diet in survivorship is highlighted by data suggesting improvement in overall survival among breast cancer survivors who adhere to healthy dietary habits ( 67 ). Unfortunately, the majority of breast cancer survivors fail to adhere to ACS dietary recommendations ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional aspect, indeed, has an important role in the prevention of cancer recurrences. Even though the impact of the Mediterranean diet on BC recurrence and progression is still under investigation 47 , there is evidence that the Mediterranean diet could reduce the recurrence risk of BC by reducing chronic inflammation 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that adhering to healthy diets can enhance overall quality of life, reduce symptoms, and even lower the risk of recurrence. Conversely, high adherence to unhealthy or Western dietary patterns has been linked to increased overall mortality [13][14][15]. Additionally, patients who adhered to their prescribed diets showed a slight improvement in physical function, as indicated by t-tests.…”
Section: Discussionmentioning
confidence: 99%